Neonatal Fc receptor-targeted lignin-encapsulated porous silicon nanoparticles for enhanced cellular interactions and insulin permeation across the intestinal epithelium - Martins João P.; Figueiredo Patrícia; Wang Shiqi; Espo Erika; Celi Elena; Martins Beatriz; Kemell Marianna; Moslova Karina; Mäkilä Ermei; Salonen Jarno; Kostiainen Mauri A.; Celia Christian; et al. (KeAi Communications Co., 2022)
Oral insulin delivery could change the life of millions of diabetic patients as an effective, safe, easy-to-use, and affordable alternative to insulin injections, known by an inherently thwarted patient compliance. Here, we designed a multistage nanoparticle (NP) system capable of circumventing the biological barriers that lead to poor drug absorption and bioavailability after oral administration. The nanosystem consists of an insulin-loaded porous silicon NP encapsulated into a pH-responsive lignin matrix, and surface-functionalized with the Fc fragment of immunoglobulin G, which acts as a targeting ligand for the neonatal Fc receptor (FcRn). The developed NPs presented small size (211 ± 1 nm) and narrow size distribution. The NPs remained intact in stomach and intestinal pH conditions, releasing the drug exclusively at pH 7.4, which mimics blood circulation. This formulation showed to be highly cytocompatible, and surface plasmon resonance studies demonstrated that FcRn-targeted NPs present higher capacity to interact and being internalized by the Caco-2 cells, which express FcRn, as demonstrated by Western blot. Ultimately, in vitro permeability studies showed that Fc-functionalized NPs induced an increase in the amount of insulin that permeated across a Caco-2/HT29-MTX co-culture model, showing apparent permeability coefficients (Papp) of 2.37 × 10−6 cm/s, over the 1.66 × 10−6 cm/s observed for their non-functionalized counterparts. Overall, these results demonstrate the potential of these NPs for oral delivery of anti-diabetic drugs.